MENINGKATKAN PERAN PEMANGKU KEPENTINGAN DALAM PENGELOLAAN WILAYAH HULU DAERAH ALIRAN SUNGAI CILIWUNG - Iis Alviya; Elvida Yosefi Suryandari; Retno Maryani; Zahhrul Muttaqin (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
Stakeholders have a ver y important role interm of  the management of  upstream watershed. Thus, the common understanding on the existence and role of  stakeholders is an important factor in order to achieve good governance of  watershed management, leading to the attainment of  environmental, social and economic benefits. This paper aims to analyse the role, interests, and cooperation among stakeholders and its relationship with the condition of  upper Ciliwung watershed. Stakeholder analysis was used in this study to identify stakeholders, to categorize them, and to investigate the relationship between stakeholders. The analysis showed the lack of  cooperation among stakeholders both between key stakeholders with primar y stakeholders. This resulted in lack of  communities' understanding on the benefits and the importance of  conservation activities in the upstream Ciliwung watershed. Meanwhile, the cooperation between key stakeholders and supporting stakeholders, especially the providers of  funds, was relatively better/stronger. This can be seen from a better management of  inter-agency cooperation in the upstream Ciliwung watershed, although the effort was tend to be project-oriented. Therefore, communication forum need to be established, to taking role for synchronizing , collaborating and coordinating stakeholders' efforts, so that the management programs of  upstream Ciliwung watershed can be integrated.